Ridiculous for govt to deny our diploma students, yet accept foreign - Daily Express, (KK) (Daily Express, 2012)
I AM a parent of two kids who studied at private institutions of higher learning (IPTS) in the country. Having completed their Diploma level studies, they are now out in the job market.